Religious freedom in the context of Islamic da'wa - Safrodin Safrodin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2022)
Purpose - This paper aims to explain religious freedom in the context of Islamic Da’wa according to the interpretation of the Qur'an.Method - This study used a qualitative approach to literature (library research) with thematic methods.Result - The results of this study have explained that religious freedom is one of the values guaranteed in Islamic Da’wa. In addition to strictly prohibiting religious coercion on everyone, the Qur'an also clarifies the limits of the missionary duties of the Prophets and scholars (dā'i), which is only to convey the truth of Islamic teachings continuously to humanity by calling on them with the wisdom, the good advice ( mauidzah hasanah ), the best dialogue (jidāl ahsan), and the good example (qudwah hasana ). The Qur'an also emphasizes the diversity of human attitudes in accepting Islamic Da’wa is a sunnah of Allah SWT ., so any attempt to force them to become believers is impossible. The essence of this meaning is at least contained in the interpretation of al-Baqarah: 256, Yūnus : 99 and al-Gāsyiyah : 21-22.Implication - This study suggests a humanist Da’wa that always respects the freedom of mad'u in determining their religion without any element of coercion.Originality - This study is the first study that tries to analyze religious freedom from the perspective of Islamic Da’wa.***Tujuan - Tulisan ini bertujuan untuk menjelaskan kebebasan beragama dalam konteks dakwah Islam menurut tafsir Al-Qur'an.Metode – Penelitian ini menggunakan pendekatan kualitatif kepustakaan (library research) dengan metode tematik.Hasil - Hasil penelitian ini menjelaskan bahwa kebebasan beragama merupakan salah satu nilai yang dijamin dalam dakwah Islam. Selain secara tegas melarang pemaksaan agama pada setiap orang, Al-Qur'an juga menjelaskan batasan tugas dakwah para Nabi dan ulama (dā'i), yaitu hanya menyampaikan kebenaran ajaran Islam secara terus menerus kepada umat manusia dengan menyeru mereka. dengan hikmah, nasehat yang baik (mauidzah hasanah), dialog yang baik (jidāl ahsan), dan teladan yang baik (qudwah hasanah). Al-Qur'an juga menekankan keragaman sikap manusia dalam menerima dakwah Islam sebagai sunnah Allah swt., sehingga upaya apapun untuk memaksa mereka menjadi beriman tidak mungkin dilakukan. Esensi makna ini setidaknya terkandung dalam tafsir al-Baqarah: 256, Yūnus : 99 dan al-Gāsyiyah : 21-22.Implikasi - Kajian ini menyarankan dakwah humanis yang selalu menghargai kebebasan mad'u dalam menentukan agamanya tanpa ada unsur paksaan.Orisinalitas - Kajian ini merupakan studi pertama yang mencoba menganalisis kebebasan beragama dalam perspektif dakwah Islam.